Problem-Based Learning Model Based on Sustainable Development Goals in School Field Introduction Program - Hikmawati; Nanda Sulistia Wardani; Suryadi Suryadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to describe the implementation of the Problem Based Learning model on circular motion material based on Sustainable Development Goals in the School Field Introduction Program as part of the Impact Campus Program. The study used a quantitative descriptive approach implemented at SMA Negeri 7 Mataram in the odd semester of the 2025/2026 academic year. The research subjects consisted of 33 students of grade XI Phase F. Data collection was carried out through essay tests and observations. The research instruments included tests based on Higher Order Thinking Skills at the level of analyzing, evaluating, and creating, as well as observation sheets for aspects of attitudes and skills. Data were analyzed using descriptive statistics through the calculation of averages, percentages, and interpretation of learning outcome categories. The results showed that the implementation of problem-based learning had a positive impact on student learning outcomes in the aspects of knowledge, attitudes, and skills, all of which were in the very good category. Students showed development in higher-order thinking skills, character strengthening according to the Pancasila Student Profile, and science process skills. The research findings show that problem-based learning is able to create active, contextual, and meaningful physics learning, while also representing the real implementation of the Impact Campus Program in supporting quality and sustainable education.